Occupant comfort assessment of wind-sensitive structures using different building codes - Garcia, Lindsay Anne F.; Hernandez, Jaime Y. Jr.; Tungol, Ian Howell S. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
The main objective of this study is to implement an occupant comfort assessment on high-rise structures in Metro Manila using different building codes. This is done to validate the assessment procedure that includes a field vibration test and motion sickness susceptibility questionnaire. The procedure was successful in obtaining the field vibration measurements of 4 different high-rise structures in Metro Manila. However, the occupant survey was not conducted in any of the buildings since the building administrations did not allow it. All of the buildings that were tested in ambient conditions were well below the perception and comfort thresholds of all the building codes used. Although the 5 different standards produced different values of acceleration, the assessment using their respective limits are similar. Starting from PSWS 3, all of the towers were predicted to produce perceptible motion. The minimum wind speed for PSWS 3 is only 100kph while the design wind speed from the NSCP is 250kph. Graphs were also used to illustrate the effect of different response acceleration parameters of the AIJ and AS/NZS. AIJ accelerations for the along-wind direction are generally higher than AS/NZS accelerations while AS/NZS acceleration values are mostly higher than AIJ for the across-wind direction.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Tall buildings -- Aerodynamics; Tall buildings -- Vibration; Human comfort